Marginal microleakage of resin-modified glass-ionomer and composite resin restorations: Effect of using etch-and-rinse and self-etch adhesives - Maryam Khoroushi (Indian Journal of Dental Research, 2012)
Objectives: Previous studies have shown that dental adhesives increase the bond strength of resin-modified glass-ionomer (RMGI) restorative materials to dentin. This in vitro study has evaluated the effect of etch-and-rinse and self-etch bonding systems v/s cavity conditioner, and in comparison to similar composite resin restorations on maintaining the marginal sealing of RMGI restorations. Materials and Methods: 98 rectangular cavities (2.5×3×1.5 mm) were prepared on buccal and palatal aspects of 49 human maxillary premolars, randomly divided into 7 groups (N=14). The cavities in groups 1, 2 and 3 were restored using a composite resin (APX). The cavities in groups 4, 5, 6 and 7 were restored using a resin-modified glass-ionomer (Fuji II LC). Before restoring, adhesive systems (Optibond FL = OFL, three-step etch-and-rinse; One Step Plus = OSP, two-step etch-and-rinse; Clearfil Protect Bond = CPB, two-step self-etch) were used as bonding agents in groups 1-6 as follow: OFL in groups 1 and 4, OSP in groups 2 and 5, and CPB in groups 3 and 6, respectively. The specimens in group 7 were restored with GC cavity conditioner and Fuji II LC. All the specimens were thermo-cycled for 1000 cycles. Microleakage scores were determined using dye penetration method. Statistical analyzes were carried out with Kruskal-Wallis and Mann-Whitney U tests (α=0.05). Results: There were significant differences in microleakage scores at both enamel and dentinal margins between the study groups (P<0.05). The lowest microleakage scores at enamel and dentin margins of RMGI restorations were observed in group 6. Conclusion: Use of two-step self-etch adhesive, prior to restoring cervical cavities with RMGIC, seems to be more efficacious than the conventional cavity conditioner in decreasing marginal microleakage.